2010
DOI: 10.1371/journal.pone.0014224
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Resting Neural Connectivity during Propofol Sedation

Abstract: BackgroundThe default mode network consists of a set of functionally connected brain regions (posterior cingulate, medial prefrontal cortex and bilateral parietal cortex) maximally active in functional imaging studies under “no task” conditions. It has been argued that the posterior cingulate is important in consciousness/awareness, but previous investigations of resting interactions between the posterior cingulate cortex and other brain regions during sedation and anesthesia have produced inconsistent results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
157
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(169 citation statements)
references
References 69 publications
(111 reference statements)
10
157
2
Order By: Relevance
“…Evidence for reduced coupling between posterior, parietal, and frontal cortices was reported in recent studies during deep NREM sleep (Horovitz et al, 2009;Sämann et al, 2011) and anesthesia (Boveroux et al, 2010;Schrouff et al, 2011). Reorganized connectivity of posterior nodes, such as PCC, has been reported already for moderate levels of propofol (Stamatakis et al, 2010). …”
Section: Effects Of Pi-loc On Subcortical and Cortical Functional Conmentioning
confidence: 86%
See 1 more Smart Citation
“…Evidence for reduced coupling between posterior, parietal, and frontal cortices was reported in recent studies during deep NREM sleep (Horovitz et al, 2009;Sämann et al, 2011) and anesthesia (Boveroux et al, 2010;Schrouff et al, 2011). Reorganized connectivity of posterior nodes, such as PCC, has been reported already for moderate levels of propofol (Stamatakis et al, 2010). …”
Section: Effects Of Pi-loc On Subcortical and Cortical Functional Conmentioning
confidence: 86%
“…While early fMRI studies of BOLD signal fluctuations across levels of consciousness reported persistent intrinsic activity and relatively preserved spatial organization during light sleep and sedation (Greicius et al, 2008;Horovitz et al, 2008;LarsonPrior et al, 2009), recent studies point to a state-dependent modulation: during propofol-anesthesia, a linear association between functional connectivity of frontoparietal networks and levels of consciousness (Boveroux et al, 2010), a reorganization of key nodes of the default mode network (Stamatakis et al, 2010), and decreased subcortical-cortical connectivity have been reported (Mhuircheartaigh et al, 2010). State-dependent changes in functional connectivity have also been observed during deep NREM sleep (Horovitz et al, 2009;Sämann et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Suppressed frontoparietal and thalamic activity appear to be a common finding in most anesthesia studies (Kaisti et al, 2002;Baars et al, 2003;Bonhomme et al, 2008;Mhuircheartaigh et al, 2010;Stamatakis et al, 2010;Schrouff et al, 2011;Tu et al, 2011). These changes have generally been interpreted directly as neural correlates for LOC.…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies have now examined the connectivity effects associated with changing levels of consciousness (Imas et al, 2005;Massimini et al, 2005;Boveroux et al, 2010;Mhuircheartaigh et al, 2010;Stamatakis et al, 2010;Boly, 2011;Boly et al, 2011;Schrouff et al, 2011). It has been hypothesized that decreased frontal to parietal feedback is a likely correlate for the diminished consciousness associated with sleep (Massimini et al, 2005), brain injury , and anesthesia (Imas et al, 2005;Alkire et al, 2008;Ku et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation